Clinically Oriented Anatomy - Moore, Keith L., Dalley, Arthur F. (2006)
Clinically Oriented Anatomy has been widely acclaimed for the relevance of its clinical correlations. As in previous editions, the fifth edition places clinical emphasis on anatomy that is important in general practice, diagnostic radiology, emergency medicine, and general surgery. Special attention has been directed toward assisting students in learning the anatomy they will need to know in the twenty-first century, and to this end new features have been added and existing features updated